Polytypism of Ln(SeO3)(HSeO3)·2H2O compounds: synthesis and crystal structure of the first monoclinic modification of Nd(SeO3)(HSeO3)·2H2O, DFT calculations and order/disorder description. Issue 2 (15th March 2023) - Murtazoev, Alisher F.; Berdonosov, Peter S.; Aksenov, Sergey M.; Kuznetsov, Alexey N.; Dolgikh, Valery A.; Nelyubina, Yulia V.; Merlino, Stefano
Abstract : The crystal structures of Nd(SeO3 )(HSeO3 )·2H2 O polymorphs show order–disorder (OD) character and can be described using the same OD groupoid family. The structural complexity parameters and DFT calculations of both polytypes show that the polytype structures are extremely close energy‐wise and almost equally viable from the point of total energy of the structure. Abstract : Compounds with the general formula Ln 3+ (SeO3 )(HSeO3 )·2H2 O, where Ln = Sm 3+, Tb 3+, Nd 3+ and Lu 3+, are characterized by orthorhombic symmetry with space group P 21 21 21 and unit‐cell parameters in the ranges a ∼ 6.473–6.999, b ∼ 6.845–7.101, c ∼ 16.242–16.426 Å. Light‐purple irregularly shaped crystals of a new monoclinic polytype of neodymium selenite Nd(SeO3 )(HSeO3 )·2H2 O have been obtained during a mild‐condition hydrothermal synthesis. The monoclinic unit‐cell parameters are: a = 7.0815 (2), b = 6.6996 (2), c = 16.7734 (5) Å, β = 101.256 (1)°, V = 780.48 (6) Å 3 ; space group P 21 / c . The crystal structures of Nd(SeO3 )(HSeO3 )·2H2 O polymorphs show order–disorder (OD) character and can be described using the same OD groupoid family, more precisely a family of OD structures built up from two kinds of non‐polar layers (category IV). The first monoclinic maximum degree order (MDO) structure (MDO1‐polytype) with space group P 21 / c can be obtained when the inversion centre is active in the L 2 n ‐type layers, while the second MDO structure (MDO2‐polytype) is orthorhombic with space group P 21 21 21 and can be obtained when the [21 ‐‐] operation is active in the L 2 n ‐type layers. The structural complexity parameters and DFT calculations of both polytypes show that the polytype structures are extremely close energy‐wise and almost equally viable from the point of total energy of the structure.